2015
DOI: 10.4238/2015.may.11.4
|View full text |Cite
|
Sign up to set email alerts
|

Values for serum procalcitonin, C-reactive protein, and soluble triggering receptor expressed on myeloid cells-1 in predicting survival of patients with early-onset stroke-associated pneumonia

Abstract: ABSTRACT. We examined the value of serum procalcitonin (PCT), C-reactive protein (CRP), soluble triggering receptor expressed on myeloid cells-1 (sTREM-1) for predicting the survival of patients with early-onset stroke associated pneumonia (EOP). A total of 207 stroke patients were enrolled, and 91 developed EOP. Upon admission, serum PCT, CRP, sTREM-1 levels, clinical pulmonary infection score, and Acute Physiology and Chronic Health Evaluation II score were all significantly higher in patients with EOP than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 14 publications
(13 reference statements)
0
5
0
Order By: Relevance
“…In the process of lung inflammation, sTREM-1 is an indispensable regulator. In normal lung tissues, sTREM-1 is selectively expressed by pathogen-clearing alveolar macrophages and is upregulated in the presence of bacteria and fungi [33,34]. Studies have shown that the expression level of sTREM-1 in bronchial lavage fluid of patients with community-acquired pneumonia and hospital-acquired pneumonia is significantly higher than that of healthy controls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the process of lung inflammation, sTREM-1 is an indispensable regulator. In normal lung tissues, sTREM-1 is selectively expressed by pathogen-clearing alveolar macrophages and is upregulated in the presence of bacteria and fungi [33,34]. Studies have shown that the expression level of sTREM-1 in bronchial lavage fluid of patients with community-acquired pneumonia and hospital-acquired pneumonia is significantly higher than that of healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that the expression level of sTREM-1 in bronchial lavage fluid of patients with community-acquired pneumonia and hospital-acquired pneumonia is significantly higher than that of healthy controls. In addition, the level of sTREM-1 is correlated with the positive rate of blood culture and sputum culture in patients with community-acquired pneumonia, indicating that serum sTREM-1 can be used as an independent inflammatory indicator of pneumonia [34,35]. CXCL-16 can chemotactically recruit lymphocytes by binding to its receptor CXCR6 to participate in the body's immune regulation [36].…”
Section: Discussionmentioning
confidence: 99%
“…In these studies, inflammatory biomarkers, such as the neutrophil-to-lymphocyte ratio (NLR) and monocyte-to-lymphocyte ratio (MLR), were explored to predict SAP (Cheng et al, 2020;Nam et al, 2018). C-reactive protein (CRP), interleukin-6 (IL-6), and procalcitonin (PCT) have also been shown to be associated with SAP and can be used as predictors of SAP (Kwan et al, 2013;Xie et al, 2015). The hypersensitive C-reactive protein-albumin ratio (CAR) is calculated from hypersensitive C-reactive protein (Hs-CRP), and albumin (ALB) has been reported…”
Section: Introductionmentioning
confidence: 99%
“…In these studies, inflammatory biomarkers, such as the neutrophil‐to‐lymphocyte ratio (NLR) and monocyte‐to‐lymphocyte ratio (MLR), were explored to predict SAP (Cheng et al., 2020 ; Nam et al., 2018 ). C‐reactive protein (CRP), interleukin‐6 (IL‐6), and procalcitonin (PCT) have also been shown to be associated with SAP and can be used as predictors of SAP (Kwan et al., 2013 ; Xie et al., 2015 ). The hypersensitive C‐reactive protein‐albumin ratio (CAR) is calculated from hypersensitive C‐reactive protein (Hs‐CRP), and albumin (ALB) has been reported as a new and sensitive marker and is associated with poor outcomes in patients with tumors or cancer, critically ill patients, and patients with various brain diseases, such as spontaneous intracerebral hemorrhage (Bender et al., 2020 ; Park et al., 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, stroke is often accompanied by an inflammatory response that could lead to an imbalance in the system that regulates body temperature; this may increase body temperature, reduce immunity, and increase the risk of pathogenic infection and invasion of the lungs, thus aggravating the inflammatory response and immune response disorders. Collectively, these events may lead to a further increase in body temperature and the levels of CRP and PCT, thus increasing the risk of pneumonia ( 18 ). OASIS is a comprehensive evaluation index based on 10 parameters, including age, body temperature, and urine volume on the 1st day of ICU.…”
Section: Discussionmentioning
confidence: 99%